Adaptasi Sosial Tokoh Mikami dalam Film Subarashiki Sekai karya Miwa Nishikawa - Zaki Ainul Fadli; Nezatria Risma Quartyza (IZUMI, 2022)
This research was conducted to reveal and classify the social adaptation efforts made by the main character in the film "Subarishiki Sekai" by Miwa Nishikawa. This type of research is quantitative research with a literary sociological approach. The theory used is Robert K. Merton‘s typology of adaptation. Data is collected by the listening and record method. The stages of adaptation according to Merton there are five, namely conformity, innovation, ritualism, retreatism, and rebellion. The results showed that from the five stages of adaptation, Mikami only performed the following four stages: (1) conformity, changing the way you look, looking for job openings, buying the latest mobile phone, studying for a driving exam; (2) innovation, biting the stomach of a thug who locks an employee at night; (3) ritualism, not saving and laughing at Abe when other employees bullied and made fun of Abe; (4) Retreatism, go to Kyushu to isolate themselves when all Mikami’s efforts did not get the response he expected. The conclusion of this study is that social adaptation must be done by ex-convicts who want to blend back into society. In particular, the state and society must play a role and be present in helping ex-convicts to obtain jobs and re-mingle with society so that they do not return to illegal business or crime.